"A few good men": Public sector audit in the Swan River Colony, 1828–1835. (May 2013) - Bunn, Michelle; Gilchrist, David J
The appointment of the Auditor General to undertake public sector audit is the primary instrument used to safeguard public finances in most contemporary Westminster-based democracies. It is axiomatic that the independence of the Auditor General from executive government is a critical element in ensuring the effectiveness of the role, yet this separation is a relatively recent phenomenon. Those responsible for nineteenth century public sector audit in the Australian colonies operated in what would today be considered an unacceptable environment, with little, if any, independence from the executive arm of government. Yet, while several other Australian colonies suffered from the mismanagement of government finances, there is nothing to show that the Swan River Colony experienced much more than clerical errors and minor administrative oversights. In this article, we explore the extent to which satisfactory public financial management in the Swan River Colony occurred as a result of both good financial management systems (in the context of the era) and the appointment of competent and ethical administrators – "a few good men".